Identification of Wheat Flour Segmentation Based on Household Consumer's Preferences - Ivonny Erlandharosi; Wahyu Supartono; Didik Purwadi (agriTECH, 2002)
The aim of this study research was to indentify wheat flour segmentation based on household consumer. Samples of this research were CK, KB and SB. The research method was "Stratified Random Sampling". Respondents for questionaire were chosen from consumers who were divided into three level based on welfare society of BKKBN Yogyakarta called higher, middle and lower consumer welfare. The three different level society had different decision to buy products for their need. The segmentation due to the consumer need was needed to homogenize their needs. The result of this research showed that there was an interantion between level of society's welfare and knowledge of wheat flour utilization. It mean that the highest class level knew more about wheat flour utilization. The processed product depended on chosen brand of wheat flour, but there was not an interaction between consumer society level and the chosen product brand of wheat flour. Consumer had difference knowlegde on utilization of CK and KB. For lower and middle class level, and middle and higher class level had similar decision of wheat flour utilization. For higher and lower class level, there was difference knowledge of utilization of wheat flour KB.